Tradisi dan Modernitas Perspektif Seyyed Hossein Nasr - Encung Encung (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2012)
This article is intended to scrutinize Seyyed Hossein Nasr’s thought about the negative dimensions of modernity and put it into the world's problems where the idea of materialism ends due to the greed of modern people. Nasr’s aim is actually to save humanity from destructive elements of modernity due to the idea of materialism. However, the traditional-ism project that he proposed has still looked for momentum within human consciousness and that is not to neglect the sacred matter in understanding their world. In a reflection of his traditionalism, Nasr presupposes the creation of a progressive world presented with the self-awareness of the Absolute and the Infallible existence. Nasr believes that modern people could live with their idea of perennial philosophy that connects everything in this world into the sacred realm. The benefits of modernity, according to Nasr, will be tarnished if people deny every sacred matter.